Non-state initiatives on enhancing counter-trafficking of Rohingya influx in Cox's Bazar of Bangladesh - Alam, Edris; Molla, Morshed Hossan; Islam, Md. Kamrul; Rahman, Md. Arifur; Barua, Jishu (Frontiers in Public Health, 2023)
Human trafficking is the third most lucrative form of trafficking in the world (just behind drugs and counterfeit goods). Multiple outbreaks of unrest between October 2016 and August 2017 in the Rakhine State of Myanmar triggered around 745,000 influxes of Rohingyas crossing into Bangladesh through the border boundaries at Teknaf and Ukhiya sub-districts of Cox’s Bazar. In this regard the media confirmed that over a thousand Rohingya people particularly women and girls were victims of human traffickers. This research aims to explore the underlying cause of human trafficking (HT) during emergency response and seeks how the knowledge and capacity of the refugee, local administration and law enforcement agencies in Bangladesh can be improved in promoting counter trafficking (CT) and safe migration processes. In order to achieve the objectives, this research starts with reviewing acts, rules, policies and action plans of the Government of Bangladesh on the HT, CT and safe migration processes. Then, a case study method has been applied to present ongoing the CT and safe migration programs of a NGO called Young Power in Social Action (YPSA) that received funding and technical support from the International Organization of Migration (IOM) for this purpose, the research in this paper will later evaluate the effectiveness of the program through conducting key informant interviews (KII) and focus group discussion (FGDs) with beneficiary and non-beneficiary participants from refugees, law-enforcing agencies (LEA) and non-governmental organizations’ (NGOs) in Teknaf, and Ukhyia sub-districts in Bangladesh. Thus, this research identified program level strengths and weaknesses in relation to the CT, and safe migration process and provide key directions how they can be improved.